1986
DOI: 10.1016/0014-5793(86)81142-5
|View full text |Cite
|
Sign up to set email alerts
|

The activated human met gene encodes a protein tyrosine kinase

Abstract: We have raised antibodies against a synthetic dodecapeptide corresponding to the carboxyl terminus of the predicted met gene product. Phosphorylation of 60 kDa and 65 kDa proteins on tyrosine residues was observed when immunoprecipitates of cells containing the activated human met gene were incubated with [Y-~~P]ATP. Phosphoproteins with the same molecular masses could be immunoprecipitated from cells metabolically labelled with [32P]orthophosphate. When considered together, these observations indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…(Park et al, 1986a). In agreement with the results of our previous study (Tempest et al, 1986b) (Park et al, 1987) revealed the interesting sequence Lys-Arg-Lys-Lys-Arg-Ser 303 amino acids from the amino terminus. This basic amino acid sequence is similar to the sequence Arg-Lys-Arg-Arg-Ser found at the cleavage site of the insulin receptor precursor (Ullrich et al, 1985) and to the sequence Arg-Lys-Arg-Arg-Asp found at the cleavage site of the precursor of the insulin-like growth factor I receptor (Ullrich et al, 1986).…”
Section: Antibodiessupporting
confidence: 93%
See 3 more Smart Citations
“…(Park et al, 1986a). In agreement with the results of our previous study (Tempest et al, 1986b) (Park et al, 1987) revealed the interesting sequence Lys-Arg-Lys-Lys-Arg-Ser 303 amino acids from the amino terminus. This basic amino acid sequence is similar to the sequence Arg-Lys-Arg-Arg-Ser found at the cleavage site of the insulin receptor precursor (Ullrich et al, 1985) and to the sequence Arg-Lys-Arg-Arg-Asp found at the cleavage site of the precursor of the insulin-like growth factor I receptor (Ullrich et al, 1986).…”
Section: Antibodiessupporting
confidence: 93%
“…Other cell lines such as the CaLu-I lung tumour line contain both 9.0 kb and 7.0 kb mRNAs while the most complex pattern of transcription of the normal met gene is present in MNNG-HOS cells and in the parent HOS cell line, which both contain 9.0 kb, 7.0 kb and 6.0 kb mRNA species. Most B-cell and T-cell tumour lines do not contain detectable levels of met transcripts.Antibodies raised against synthetic peptides corresponding to the carboxyl terminus of the predicted met gene product have been used to detect proteins encoded by the activated and normal met genes (Park et al, 1986b;Tempest et al, 1986b Tempest et al (1986b), although in this particular study of low level of phosphorylation of a 165 kD protein, which probably corresponds to the 160 kD protein detected by Park et al (1986b), was also observed.As a first step in determining whether alterations in met can be implicated in the induction of human tumours we have used antipeptide antibodies to examine met protein kinase activity in a series of human tumour cell lines. In addition, to help understand the large quantitative and qualitative variations in met kinase activity observed in these experiments, we have used SDS-polyacrylamide gel electrophoresis to examine the structure of the mature met protein.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…1 (13,14). This chimeric gene is transcribed to produce a unique 5.0-kb hybrid tpr-met mRNA that is in turn translated to form a 60-to 65-kDa fusion protein in which the protein tyrosine kinase domain of met is fused to the amino-terminal region of the trp protein (13,14,29,33). The region of the trp protein present in the trp-met fusion protein exhibits weaker homology to several structural proteins, including laminin and lamin, indicating that the normal trp protein may also encode a structural protein (32).…”
Section: The Met Genementioning
confidence: 99%